Bene Israel : studies in the archaeology of Israel and the Levant during the Bronze and Iron Ages in honour of Israel Finkelstein - Fantalkin, Alexander.; Finkelstein, Israel.; Yasur-Landau, Assaf. (Culture and History of the Ancient Near East, 2008)
This collection of twelve papers, dedicated to Professor Israel Finkelstein, deals with various aspects concerning the archaeology of Israel and the Levant during the Bronze and Iron Ages. Although the area under discussion runs from southeastern Turkey (Alalakh) down to the arid zones of the Negev Desert, the main emphasis is on the Land of Israel. This collection provides the most recent evaluation of a number of thorny issues in Israeli archaeology during the Bronze and Iron Ages and specifically addresses chronology, state formation, identity, and agency. It offers, inter alia, a fresh look at the burial practices and iconography of the periods disscussed, as well as a re-evaluation of the subsistence economy and settlement patterns. This book is finely illustrated with more than sixty original drawings. "...I cannot but emphasize that this volume contains a collection of very interesting and, in some cases, important studies on the archaeology of the Bronze and Iron Age Levant, a fitting tribute to a consummate teacher and researcher." Aren M. Maeir, Bar-Ilan University